PENGEMBANGAN MODEL PELATIHAN APRESIASI SENI TARI TRADISI LOKAL PADA GURU DI SEKOLAH DASAR - Wahira, Wahira (Universitas Negeri Semarang, 2011)
The aims of this development are (1) to describe the art of dance training model which have ever given, (2) to describe of training needs of the appreciation of local dance for the teacher of elementary school, (3) to describe first draft of the appreciation of local dance training model for the elementary school teacher, (4) to describe the result of the first design of draft model and set of appreciation training of local dance for the elementary school teacher, (5) to describe the result of expert team evaluation (expert of management, art, and lecture of the art of dance) to the model of training set which is useful for elementary school teacher training; (6) to describe the limited trial result of the implementation of appreciation training model of local dance for elementary school teacher; (7) to describe the appreciation training model of local dance which is developed after getting the trial. The research method is Research and Development (R & D). The implementation of model uses single one shot case study design with one group pre-test and post-test. Survey respondents are primary school teachers in Makassar. Data collection interview and questionnaires. Effectiveness of the model is tested through test validation by experts and practitioners, as well as a limited experiment through training. And, the data is analyzed descriptively. The findings of this study are the aspects which affect the needs and success of ASTNDS training implementation. They are: (1) training materials, (2) training programs, (3) the form of training, (4) training instructor, (5) training facilities & infrastructure, and (6) CD of dance training. Other findings are generating ASTNDS training model and devices which refers to management functions (2-steps planning; 4-steps implementation, and 2-steps evaluation). Validation and experimental test results show that the model of a hypothetical model of local dance is effective for primary school teachers training. Researcher recommends applying ASTNDS model and training devices in a primary school teacher training because it is proved that it is effective for teacher training on the subject of art, culture and skills in elementary schools.